2014
DOI: 10.1515/auk-2014-0108
|View full text |Cite
|
Sign up to set email alerts
|

Physische Attraktivität und soziale Ungleichheit. Einige grundsätzliche Anmerkungen zu einem in der soziologischen Forschung kaum beachteten Prädiktor sozialer Ungleichheit

Abstract: Physische Attraktivität und soziale Ungleichheit. Einige grundsätzliche Anmerkungen zu einem in der soziologischen Forschung kaum beachteten Prädiktor sozialer Ungleichheit Abstract: The external appearance of a person is an important predictor for his or her social success. This nding has been veried by numerous mostly social psychological oriented empirical studies on physical attractiveness for many phases and areas of life. At the same time, sociological research on social inequality has hardly paid any at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Despite the lack of multiple raters, many studies using the same measurements as we do find significant effects of attractiveness which match results from studies relying on multiple raters (see for example Gupta et al, 2016 compared to Hamermesh and Abrevaya, 2013 for happiness, or Pfeifer, 2012 compared to Judge et al, 2009 for income). Rosar et al (2014: 191–192) even assume that effects found using a somewhat limited attractiveness measurement would only manifest more clearly when based on a superior measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the lack of multiple raters, many studies using the same measurements as we do find significant effects of attractiveness which match results from studies relying on multiple raters (see for example Gupta et al, 2016 compared to Hamermesh and Abrevaya, 2013 for happiness, or Pfeifer, 2012 compared to Judge et al, 2009 for income). Rosar et al (2014: 191–192) even assume that effects found using a somewhat limited attractiveness measurement would only manifest more clearly when based on a superior measurement.…”
Section: Methodsmentioning
confidence: 99%